2013
DOI: 10.1128/aem.03400-12
|View full text |Cite
|
Sign up to set email alerts
|

RubisCO Gene Clusters Found in a Metagenome Microarray from Acid Mine Drainage

Abstract: bThe enzyme responsible for carbon dioxide fixation in the Calvin cycle, ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO), is always detected as a phylogenetic marker to analyze the distribution and activity of autotrophic bacteria. However, such an approach provides no indication as to the significance of genomic content and organization. Horizontal transfers of RubisCO genes occurring in eubacteria and plastids may seriously affect the credibility of this approach. Here, we presented a new method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Levic an et al (2008) reported that Acidithiobacillus spp., but not Leptospirillum spp., harbor genes encoding phosphoribulokinase and sedoheptulose-1,7-bisphosphatase (Table 2). Several forms of Rubisco, one of the most important enzymes involved in the first rate-limiting step of CO 2 fixation (Ellis, 1979), have been identified (I-IV) (Tabita et al, 2007;Guo et al, 2013). Form I Rubisco, which is present in most photo-and chemoautotrophic organisms, is reportedly a hexadecamer containing eight large and eight small subunits (L 8 S 8 ), while form II Rubisco comprises only large subunits (L n ).…”
Section: Carbon Assimilationmentioning
confidence: 99%
“…Levic an et al (2008) reported that Acidithiobacillus spp., but not Leptospirillum spp., harbor genes encoding phosphoribulokinase and sedoheptulose-1,7-bisphosphatase (Table 2). Several forms of Rubisco, one of the most important enzymes involved in the first rate-limiting step of CO 2 fixation (Ellis, 1979), have been identified (I-IV) (Tabita et al, 2007;Guo et al, 2013). Form I Rubisco, which is present in most photo-and chemoautotrophic organisms, is reportedly a hexadecamer containing eight large and eight small subunits (L 8 S 8 ), while form II Rubisco comprises only large subunits (L n ).…”
Section: Carbon Assimilationmentioning
confidence: 99%
“…However, considerable progress has been made toward expressing bacterial homologs of the eukaryotic enzymes in tobacco [18,19], which holds promise for introducing artificially evolved bacterial enzymes in higher eukaryotes. This could be facilitated by recent studies in which metagenomic sampling has identified potentially novel RubisCOs from microbial 'dark matter' [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…7). These sequences were closely related to uncultured clones isolated from AMD (100 % sequence similarity, accession number: JX297618) (Brofft et al 2002;Guo et al 2013;Mendez et al 2008) and Metallibacterium scheffleri (99 % sequence similarity of 374 bp). M. scheffleri, isolated from acidic biofilms, is able to oxidize Fe(II) and reduce Fe(III) (Ziegler et al 2013).…”
Section: Discussionmentioning
confidence: 81%